Integration of Character Values in Cultural Arts Learning in Elementary Schools - Yulia Septi Wahyuni; Yesika Novita Rahmi; Nurhanifa Tamba; Dini Susanti (Journal of Learning Improvement and Lesson Study, 2025)
This study analyzes the integration of character values in Cultural Arts learning in elementary schools, teacher strategies for instilling these values, and students’ behavioral responses and development. A descriptive qualitative approach was used with 3 Cultural Arts teachers and 78 fourth- and fifth-grade students, purposively selected. Data were collected through 12 observation sessions using a character values observation sheet, semi-structured interviews, and documentation including lesson plans (RPP), activity photos, and student artworks. Data were analyzed thematically through reduction, presentation, and conclusion drawing, with validity strengthened by source triangulation and member checking. The results indicate that the integration of character values—discipline, responsibility, cooperation, and cultural appreciation—consistently appeared in classroom activities. The most effective teacher strategies included group art projects, reflective discussions, introduction of local artifacts, and teacher role modeling. Empirical evidence showed an increase in students’ ability to appreciate peers’ work (78%), participation in discussions on local cultural symbols (70%), and student responsibility (66%), along with a decrease in disciplinary issues. These findings confirm that character-based Cultural Arts learning provides meaningful learning experiences and can serve as a model for character education implementation in elementary schools.